Ultrasonic Evaluation of "Silent Regions" in the Thyroid Scintiscan - Zollikofer, Ch. L.; Frank, Th.; Wewerka, J. (Nuklearmedizin - NuclearMedicine, 1978)
35 patients with scintigraphically silent thyroid regions without palpable cold nodules were further evaluated by ultrasonography. In 33 cases the sonographic diagnosis was confirmed by other examinations or the clinical course. 2 cases were misinterpreted right at the beginning of our series.The use of ultrasonography in evaluating silent thyroid regions in the totally decompensated autonomous adenoma, in unilateral thyroid aplasia, thyroiditis and hyperthyroidism is shown to be a reliable and valuable supplement to the clinical and radioisotopic evaluation procedures. When differentiating the totally decompensated autonomous adenoma from unilateral thyroid aplasia a stimulation test need not be performed in most cases. Suspected thyroiditis can be confirmed in a simple way. Being a non-invasive evaluation procedure, ultrasonography should be used before performing a needle biopsy.